Characteristics and Predictors for Students Classified with Emotional and Behavioral Disorder Who Have Also Experienced Maltreatment - Richard E. Mattison; Gregory J. Benner; Skip Kumm (Educational Considerations, 2021)
Though experiencing maltreatment (abuse or neglect) appears to be common in students with the special education label of emotional and behavioral disorders (EBD), little research has been devoted to this topic by EBD educators. This paper uses archived file drawer data from 1992 that focuses on 149 students newly classified with EBD for whom a wide range of enrollment variables was collected, and who were subsequently followed up on an average of 8 years later to assess their educational outcomes. At enrollment, experiences of maltreatment were determined to have occurred in 57.7% of these participants. The group who experienced maltreatment was predicted at enrollment only by the family stress of having at least one natural parent with a history of psychiatric illness, although the concordance was not strong (52.3%). When the children who experienced maltreatment were next divided into two longitudinal groups according to educational outcomes (52.3% successful), the enrollment variables of the presence of anxiety and/or depressive disorder and younger age predicted the successful outcome group with good concordance (76.0%). Professional and programmatic implications for educators of students identified with EBD who have also experienced maltreatment are discussed, along with practical recommendations for serving this population.
Keywords: emotional and behavioral disorders; emotional disability; special education; childhood maltreatment; adverse childhood experiences; childhood trauma